2015
DOI: 10.1007/s00003-015-0939-7
|View full text |Cite
|
Sign up to set email alerts
|

Food handlers: a bridge in the journey of enterotoxigenic MRSA in food

Abstract: We investigated the presence of enterotoxigenic and methicillin-resistant Staphylococcus aureus (MRSA) in a kitchen of a catering firm by collecting 100 food samples and 100 utensil-equipment samples after sanitation. Additional 186 samples in total were collected by swabbing the mouths, noses and hands of 62 kitchen staff members during working hours. The isolation of S. aureus was performed using a culture method and verified by using a genetic method (PCR). The presence of toxin genes and the toxic shock sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…Also the study showed that 42% of S. aureus carried the mecA gene (MRSA). This finding is higher than Sezer et al, 2015 [ 19 ] (28.9%), and lower than Loeto et al, 2007 (57.5%) in Botswana [ 20 ]. The high prevalence of MRSA could be due to the extensive usage of antibiotics in the Al Jazirah community without prescription.…”
Section: Discussioncontrasting
confidence: 61%
“…Also the study showed that 42% of S. aureus carried the mecA gene (MRSA). This finding is higher than Sezer et al, 2015 [ 19 ] (28.9%), and lower than Loeto et al, 2007 (57.5%) in Botswana [ 20 ]. The high prevalence of MRSA could be due to the extensive usage of antibiotics in the Al Jazirah community without prescription.…”
Section: Discussioncontrasting
confidence: 61%
“…It is possible that the worker can contaminate or carries one strain from her/his nasal cavity to her/his mouth or/and hand or vice versa. Earlier study (Sezer et al 2015 ) report that carriage rate of S. aureus among food handlers was 79 %. However, there are other studies indicating much lower prevalence among food handlers in Turkey.…”
Section: Discussionmentioning
confidence: 96%
“…The presence of S. aureus in raw or processed pig meat and the contamination of these bacteria between food handlers and these foods have been described in the literature (BUYUKCANGAZ et al, 2013;CASTRO et al, 2016;CHON;SUNG;KHAN, 2017;COSTA et al, 2015;FALL et al, 2012;SEZER et al, 2015).…”
Section: Staphylococcus Spp In Pig Farmingmentioning
confidence: 99%
“…However, the origin of S. aureus is not associated exclusively with pigs or to their environments of growth and slaughter, or to handlers of these animals, but also to handlers that assist in the production and processing of meat products. Persistent or intermittent nasal colonization by S. aureus have been found in 30% to 50% of healthy individuals (SERGELIDIS;ANGELIDIS, 2017;CASTRO et al, 2016;SEZER et al, 2015;COSTA et al, 2015;FERREIRA et al, 2014;KLUYTMANS, 2010).…”
Section: Staphylococcus Spp In Pig Farmingmentioning
confidence: 99%